2017
DOI: 10.1111/1751-2980.12551
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant chemoradiation for non‐metastatic pancreatic cancer increases margin‐negative and node‐negative rates at resection

Abstract: Neoadjuvant chemoradiation remains a promising approach for non-metastatic pancreatic cancer for improving resectability and pathological and clinical findings. Computed tomography may not fully demonstrate the effectiveness of neoadjuvant treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Joint Committee on Cancer defines tumors that involve the celiac axis and superior mesenteric artery (SMA) as T4 and surgically unresectable due to inability to render a negative margin resection with standard pancreatectomy techniques. 1 Consideration of en bloc arterial resection during pancreatectomy had been relatively abandoned for decades due to the significant risk of ischemic and hemorrhagic complications, with attendant morbidity and mortality and historically poor long-term oncologic outcomes, which were initially reported by Fortner in the 1970s. 2 However, there has been renewed interest in en bloc arterial resection for PDAC due to improved response rates and associated survival benefit with modern combination chemotherapeutic regimens with increasing use of total neoadjuvant therapy.…”
mentioning
confidence: 99%
“…Joint Committee on Cancer defines tumors that involve the celiac axis and superior mesenteric artery (SMA) as T4 and surgically unresectable due to inability to render a negative margin resection with standard pancreatectomy techniques. 1 Consideration of en bloc arterial resection during pancreatectomy had been relatively abandoned for decades due to the significant risk of ischemic and hemorrhagic complications, with attendant morbidity and mortality and historically poor long-term oncologic outcomes, which were initially reported by Fortner in the 1970s. 2 However, there has been renewed interest in en bloc arterial resection for PDAC due to improved response rates and associated survival benefit with modern combination chemotherapeutic regimens with increasing use of total neoadjuvant therapy.…”
mentioning
confidence: 99%
“…Recent RCT showed that clinical tumor staging was down-staged after treatment of gemcitabine-based CRT ( 9 ). Another study showed that neoadjuvant CRT can downstage the PC and eventually increases margin-negative and node-negative rates at resection ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…The existing data comparing CRT alone and SCT plus CRT in locally advanced disease is contradictory: in comparing SCT with and without CRT, Hugeut et al found survival benefits in patients who received SCT with CRT, while Hammal et al saw no improvement in survival in patients who received SCT and CRT (15,16). While multiple trials have compared different regimens and combinations of SCT, CRT, or both in resectable and borderline resectable pancreatic adenocarcinoma, there is still more work to elucidate the optimal treatment regimen (17)(18)(19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%